2017
DOI: 10.1186/s12969-016-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Syndrome: different mechanisms leading to a one clinical syndrome

Abstract: BackgroundMacrophage activation syndrome (MAS) is a severe complication of rheumatic disease in childhood, particularly in systemic Juvenile Idiopathic Arthritis (sJIA). It is characterize by an uncontrolled activation and proliferation of T lymphocytes and macrophages.Main contentMAS is currently classified among the secondary or acquired forms of haemophagocytic lymphohistiocytosis (sHLH). The reason is that MAS shares clinical and laboratory features with primary genetic HLH (pHLH). In this context is conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 47 publications
2
107
0
10
Order By: Relevance
“…Cytokine storm syndromes (CSS) are a group of disorders representing a variety of inflammatory etiologies with the final result of overwhelming systemic inflammation, hemodynamic instability, multiple organ dysfunction, and potentially death [208,209]. Specifically, macrophage activation syndrome [210] and hemophagocytic lymphohistiocytosis (HLH) [211] represent two clinically similar CSS with an unknown degree of etiopathogenic overlap [208]. The interaction between endothelial and immune cells could play a crucial role in COVID-19, especially in severe cases and in the late stages of the disease [212].…”
Section: Thromboembolism and Covid-19mentioning
confidence: 99%
“…Cytokine storm syndromes (CSS) are a group of disorders representing a variety of inflammatory etiologies with the final result of overwhelming systemic inflammation, hemodynamic instability, multiple organ dysfunction, and potentially death [208,209]. Specifically, macrophage activation syndrome [210] and hemophagocytic lymphohistiocytosis (HLH) [211] represent two clinically similar CSS with an unknown degree of etiopathogenic overlap [208]. The interaction between endothelial and immune cells could play a crucial role in COVID-19, especially in severe cases and in the late stages of the disease [212].…”
Section: Thromboembolism and Covid-19mentioning
confidence: 99%
“…As a result of chronic inflammation, patients with JIA suffer from joint pain, swelling, restricted range of motion and joint deformity (1). Severe extra-articular abnormalities may also accompany this disease, including uveitis, which occurs more frequently in antinuclear antibody (ANA)-positive patients and can lead to blindness, and macrophage activation syndrome (MAS), a complication of sJIA that can lead to multi-organ insufficiency and even mortality (3,4) Previous studies indicated that vitamin D played an important role in maintaining both the skeletal and immune systems (5,6). Vitamin D regulates the innate and adaptive immune systems by activating the vitamin D receptor, which is distributed widely on immune cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…MAS is a life-threatening complication of rheumatic disorders, including sJIA, adult-onset Still's disease (AOSD) and lupus. [1][2][3][4] Timely diagnosis and appropriate treatment of MAS are particularly important to improve the prognosis of MAS patients. At present, hemophagocytic lymphohistiocytosis (HLH)-2004 and HLH-2009 criteria are widely used to identify MAS associated with AOSD.…”
mentioning
confidence: 99%